Legal Review of Online Loans (Peer-to-Peer Lending) - Manalu, Hendri Saputra (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Information technology-based lending services are financial service providers that connect lenders and borrowers through electronic systems using the internet. In the era of digital economic development, society continues to innovate in providing credit and lending services, one of which is online loans. In 2016, the Financial Services Authority (OJK) issued Regulation Number POJK 40/2024 and OJK Circular Letter (SE OJK) 19/2023 concerning Information Technology-Based Lending Services. This study is a library research, which aims to collect data and information using materials available in the library. The primary data used are OJK regulations, specifically POJK 40/2024 and SE OJK 19/2023. The research employs a normative juridical approach. Data collection was conducted using documentation methods, which involve searching for and gathering data from various sources related to online loans and the theory of qarḍ. The analysis method used is deductive analysis. The results of the study indicate that the provisions on online loan contracts in OJK Regulation Number POJK 40/2024 and SE OJK 19/2023, particularly in Article 18, include agreements between the platform provider and the lender, and agreements between the lender and the borrower. These OJK regulations comply with Sharia principles because Articles 7, 8, 9, 10, and 11 discuss operational permits, making online loans legally valid and lawful. Therefore, they do not contain elements of fraud (gharar). Articles 19 and 20 discuss electronic documents that explain the contents of online loan agreements, ensuring there is no coercion, as all parties are fully informed about the terms of the agreement.